Structuration et approche métrologique d’un terroir gaulois : le secteur des Pierrières à Batilly-en-Gâtinais (Loiret) - Alexandra Cony; Rémy Wassong (Revue Archéologique du Centre de la France)
The area of Batilly-en-Gâtinais (Loiret) was the subject of numerous surveys which led to the discovery of around twenty settlements whose organization reminds us of the rural settlements of the second Iron Age. Five of them stand out because of their structure (complexe enclosure). Two of the studied sites (les Pierrières at Batilly-en-Gâtinais and la Porte de Puiseaux at Boynes) were excavated confirming their chronology (mid IInd century – mid Ist century B.C.). This body is included in an agrarian landscape. We can now ask ourselves what relationships existed between these settlements. The contribution of metrological studies reinforces the idea of an organised landscape which has been planned around a pole of attraction having been used as the exploitation headquarters: les Pierrières at Batilly-en-Gâtinais.